PENGARUH MEDIA SOSIAL TERHADAP POLA KOMUNIKASI MAHASISWA UNIVERSITAS ABDURRACHMAN SALEH SITUBONDO - Widiarti, Dian; Ramadhanti, Alifia Ayu; Hamid, Zainol Hasan; Adhitya, Dhimas; Farisi, Jufair; Putri, Dinda Purnama (Fakultas Ekonomi dan Bisnis, 2024)
Social media is one of the technological developments that has played a big role in making it easier for humans to communicate and socialize. Social media is online media that is used as a means of online social interaction on the internet. Users can communicate with each other, interact, share, network, and various other activities through social media. Communication is a process of conveying messages that involves several components or elements, such as communicator activities, messages, and communication. Communication is a very important force in human life and organizations, because it allows individuals to connect and inform each other. The research is based on the main discussion topic of the researcher's thinking about social media on student communication patterns at Abdurachman Saleh University. The data collection method used in the research was in the form of direct interviews with samples that the researchers felt were suitable as data collection media.